High prevalence of elevated clotting factor VIII in chronic thromboembolic pulmonary hypertension - Bonderman, Diana; Turecek, Peter L.; Jakowitsch, Johannes; Weltermann, Ansgar; Adlbrecht, Christopher; Schneider, Barbara; Kneussl, Meinhard; Rubin, Lewis J.; Kyrle, Paul A.; Klepetko, Walter; Maurer, Gerald; Lang, Irene M. (Thrombosis and Haemostasis, 2003)
Chronic thromboembolic pulmonary hypertension (CTEPH) is an enigmatic disorder lacking signs, symptoms and classical risk factors for venous thromboembolism.The objective of the prospective case controlled study, carried out at the Pulmonary Hypertension Unit, University Hospital Vienna, Austria, was to investigate whether plasma FVIII is elevated in CTEPH patients.The study examined 122 consecutive patients diagnosed with CTEPH. Plasma FVIII was measured and compared with plasma FVIII of healthy controls (n=82) and of patients with non-thromboembolic pulmonary arterial hypertension (PAH, n=88).Results show that CTEPH patients had higher FVIII levels than controls (233±83IU/dl versus 123±40IU/dl, p<0.0001) and PAH patients (158±61IU/dl, p<0.0001). Plasma FVIII one year after surgery (212±94IU/dl) was statistically unchanged compared with preoperative values (FVIII: 226±88IU/dl, n=25). FVIII>230IU/dl was more prevalent in CTEPH patients (41%) than in controls (5%, p<0.0001) and PAH patients (22%, p=0.022).We can conclude that elevated plasma FVIII is the first prothrombotic factor identified in a large proportion of CTEPH patients.
Keywords: Factor VIII; pulmonary embolism; thrombophilia